A study on geomorphology, mineralogy and geochemistry of the Toro Amarillo - Tortuguero and the Chirripó-Matina river system in the Atlantic Zone of Costa Rica - Seeters, R.J.M. van (1993)
50 pág, ilus, 14 tab.